(untitled) (World Bulletin of Public Health, 2024)
Rectal fistulas represent 0.8-1.2% of surgical conditions and exhibit various morphological forms, including branched or horseshoe-shaped passages, often forming after spontaneous abscess openings. Cryptoglandular rectal fistula involves chronic inflammation in the crypt, intersphincteric space, and pararectal tissue, resulting in fistula formation. The affected crypt acts as the internal fistula opening, with the external opening typically on the perineal skin, and less frequently on the buttocks, scrotum, or vagina. The prevalence ranges from 8 to 23 cases per 100,000 people, primarily affecting those aged 30 to 50, highlighting its social impact. Men are more commonly affected than women. Chronic paraproctitis usually follows acute paraproctitis and abscess drainage without infection control. Diagnosis involves rectal digital examination, button probe revision, sigmoidoscopy, dye tests, ultrasound with a rectal probe, and fistulography. Complex cases may require MRI and examination of rectal obturator function. Numerous surgical treatments exist for rectal fistulas.